Rational and Intuitive Brains in Islamic Education: Analysis of Al Ma'un Theology in the Neurosains Perspective - Nurjanah Wijayanti; Suyadi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2020)
The main problem of this research is the "saturation point" of the brain of the KH Dahlan students in learning QS Al-Ma'un. This research is interesting and original, because there is an interdisciplinary science between Islamic education and neuroscience, and no one has examined the rational and intuitive brain with Alma'u theology by KH. Ahmad Dahlan. The purpose of this study is to analyze the saturation point of Al-Ma'un learning in a neuroscience perspective. This analysis is important because the educational competence of Kemuhamamdiyahan is not just rational cognitive, but also spiritual intuitive, namely taking humanitarian action or social transformation to mobilize society based on Islamic teachings according to the religious understanding of Muhamadiyah. This research approach is qualitative type of library research. Sources of data in this study are journals, e-books, as well as books on neuroscience and books on the history of KH Ahmad Dahlan 's struggle by Junus Salam (2009). The data analysis technique was performed using content analysis. The results showed that in QS-Al-Ma'un learning, the rational brain of KH Dahlan students experienced a saturation point because it was only memorized, understood and repeated cognitively. This saturation point scientifically triggers the activation of the intuitive brain to actualize what is learned, understood and memorized into real deeds in the form of humanitarianaction to defend the poor as the message of Al-Ma'un's theology itself